Capital requirements for government bonds: Implications for bank behaviour and financial stability - Ulrike Neyer; André Sterzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
This paper analyses whether the introduction of capital requirements for bank government bond holdings increases financial stability by making the banking sector more resilient to sovereign debt crises. Using a theoretical model, we show that a sudden increase in sovereign default risk may lead to liquidity issues in the banking sector. Our model reveals that in combination with a central bank acting as a lender of last resort, capital requirements for government bonds increase the shock-absorbing capacity of the banking sector and thus the financial stability. The driving force is a regulation-induced change in bank investment behaviour.
Keywords: G28; G21; G01; 330; bank capital regulation; government bonds; sovereign risk; financial contagion; lender of last resort.